2002
DOI: 10.1046/j.1365-2141.2002.03522.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue factor and tissue factor pathway inhibitor levels in unstable angina patients during short‐term low‐molecular‐weight heparin administration

Abstract: Summary. High tissue factor (TF), tissue factor pathway inhibitor (TFPI) levels and a hypercoagulability state have been documented in unstable angina patients. We evaluated whether short-term enoxaparin administration (100 IU/kg b.i.d. for 3 d) reduces the high TF levels and the hypercoagulability state, and whether it influences the fibrinolytic system in 20 unstable angina patients. On d 3, we observed a significant reduction in TF levels both 1 h and 4 h after the morning injection ()25AE6% and )21AE7%; P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…LMW heparins furthermore inhibit the initiation of coagulation by mobilization of tissue factor pathway inhibitor from endothelial cells [24]. Short-term treatment with LMW heparins in unstable CAD has previously been shown to reduce coagulation activity with decreased levels of activated factor VII, prothrombin fragment 1 + 2 and D-dimer [14][15][16][17]. In concordance, the prolonged dalteparin treatment in the present study resulted in marked reduction of coagulation activity with significantly lower levels of all three coagulation markers, factor VIIa, prothrombin fragment 1 + 2 and D-dimer, up to 3 months after the acute phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LMW heparins furthermore inhibit the initiation of coagulation by mobilization of tissue factor pathway inhibitor from endothelial cells [24]. Short-term treatment with LMW heparins in unstable CAD has previously been shown to reduce coagulation activity with decreased levels of activated factor VII, prothrombin fragment 1 + 2 and D-dimer [14][15][16][17]. In concordance, the prolonged dalteparin treatment in the present study resulted in marked reduction of coagulation activity with significantly lower levels of all three coagulation markers, factor VIIa, prothrombin fragment 1 + 2 and D-dimer, up to 3 months after the acute phase.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in tPA/PAI-1 complex and vWF within 2 days after randomization might be a response to vascular injury, with rapid release of these two markers from depots within platelets and/ or endothelial cells [31,32]. Short-term treatment with LMW heparins has been reported to increase levels of tPA/PAI-1 complex [33] and of tPA-antigen and PAI-1 [14,34], both of which are strongly correlated with the tPA/PAI-1 complex [35]. Consistent with the previous results of short-term treatment, the levels of tPA/PAI-1 complex were higher during the prolonged dalteparin treatment in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…24 In a different trial, administration of enoxaparin increased levels of TFPI by almost 100% in patients with unstable angina. 49 Brown and Kuter 50 reported that SC administration of therapeutic doses of dalteparin resulted in a 1.3-fold increase in levels of TFPI. The effect of MW on the bioavailability of heparin has been well documented, 51 and anti-Xa activity is dependent on the MW of the heparin fractions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the way in which low‐molecular‐weight heparins exert an anticoagulant effect is probably not limited to just inhibition of FXa and FIIa. There is also evidence that administration of low‐molecular‐weight heparin effects the release of tissue factor pathway inhibitor from the endothelium, which leads to a reduction in the level of tissue factor (Lindahl et al , 1991; Gori et al, 2002). It is not clear which of these mechanisms is most important (Weitz, 1997).…”
Section: Low‐molecular‐weight Heparinmentioning
confidence: 99%